2022
DOI: 10.3390/molecules27196612
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking Charge Transfer in DNA-Templated Perylene Dimer Aggregates

Abstract: Molecular aggregates are of interest to a broad range of fields including light harvesting, organic optoelectronics, and nanoscale computing. In molecular aggregates, nonradiative decay pathways may emerge that were not present in the constituent molecules. Such nonradiative decay pathways may include singlet fission, excimer relaxation, and symmetry-breaking charge transfer. Singlet fission, sometimes referred to as excitation multiplication, is of great interest to the fields of energy conversion and quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…We conclude our analysis by considering null points in the upper-band, as depicted in Figure 3b, and their potential for SB-CS. Upper-band SB-CS may explain the curious observation of SB-CS in cofacially oriented perylene 16,23 and PDI 19,20,24 dimers (see Figure 1), where the absorption spectrum reveals H-aggregation through an attenuation of the first vibronic peak relative to the second. The spectra indicate an FE dominated lower-band (E CT − E Sd 1 > 0) with an Hlike energy level ordering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude our analysis by considering null points in the upper-band, as depicted in Figure 3b, and their potential for SB-CS. Upper-band SB-CS may explain the curious observation of SB-CS in cofacially oriented perylene 16,23 and PDI 19,20,24 dimers (see Figure 1), where the absorption spectrum reveals H-aggregation through an attenuation of the first vibronic peak relative to the second. The spectra indicate an FE dominated lower-band (E CT − E Sd 1 > 0) with an Hlike energy level ordering.…”
Section: Resultsmentioning
confidence: 99%
“…Symmetry-breaking charge separation (SB-CS) is an important photophysical process in which an optically excited molecular system with an initially symmetric charge distribution rapidly relaxes into an asymmetrically charge-separated state. SB-CS has received a great deal of attention for its central role in photosynthesis, where the charge separation event within the special pair of chlorophyll molecules drives the conversion of solar energy to chemical energy. There have also been many studies of SB-CS in simpler molecular complexes, as chronicled in some recent reviews. Intramolecular SB-CS has been reported in multipolar chromophores while inter molecular SB-CS has been observed in multichromophore complexes such as covalently linked dimers , and trimers of identical chromophores such as perylene diimide (PDI) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…30 These advantages of dye covalent templating via DNA enabled exciton delocalization in aggregates of such dye families as azo dyes, [31][32][33] merocyanines, 34 polymethine dyes, [35][36][37][38][39][40][41][42][43] squaraines, [44][45][46][47][48] and perylenes. 49 While several studies have shown that aggregates of porphyrins, [50][51][52][53][54] the most related dye family to bacteriochlorins, can be covalently templated via DNA, the extent of exciton delocalization was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“…9 While symmetry-breaking charge separation (SBCS, for reviews see 10−13 ) is rarely observed in bimolecular reactions, 14,15 SBCS has been studied extensively in weakly coupled multichromophoric architectures controlling chromophore−chromophore interactions by covalent linking (bianthryl, 16−18 assemblies of perylene, 7,19,20 perylenediimide, 1−4,21−27 and other dyes 5,28−32 ) or in suitable scaffolds. 6,33 The vast majority of these systems have been studied in fluid solutions, while solid materials could be more easily integrated into, e.g., organic photovoltaics or other devices where SBCS would enable light harvesting and charge separation in a single molecular material without the need for exciton migration to a donor−acceptor interface. Solid materials not only avoid practical problems with the integration of liquid components but might also enable efficient SBCS between unlinked chromophores due to their close proximity.…”
mentioning
confidence: 99%
“…Synthetic molecular systems undergoing charge transfer from a photoexcited chromophore to an identical moiety in the ground state, thus breaking the symmetry of the chromophore pair, keep attracting significant interest. Inspired by the special pair in photosynthetic charge separation, much of this interest emerges from prospective applications for the conversion of radiant to electrical or chemical energy via photovoltaics or artificial photosynthesis . While symmetry-breaking charge separation (SBCS, for reviews see ) is rarely observed in bimolecular reactions, , SBCS has been studied extensively in weakly coupled multichromophoric architectures controlling chromophore–chromophore interactions by covalent linking (bianthryl, assemblies of perylene, ,, perylenediimide, , and other dyes , ) or in suitable scaffolds. , …”
mentioning
confidence: 99%